2010
DOI: 10.1086/656586
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccine and Increased Risk of Pandemic A/H1N1‐Related Illness: First Detection of the Association in British Columbia, Canada

Abstract: An outbreak investigation in British Columbia during the late spring of 2009 provided the first indication of an unexpected association between receipt of TIV and pH1N1 illness. This led to 5 additional studies through the summer 2009 in Canada, each of which corroborated these initial findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 18 publications
5
58
0
Order By: Relevance
“…A reduced HI antibody response against A/California/7/2009 (H1N1) was noted in healthy adults who had previously received a seasonal influenza vaccine. This finding has been presented before in the ferret model (17) as well as in clinical studies (18,19). The mechanism is still uncertain, but the following hypothesis may be considered.…”
Section: Discussionsupporting
confidence: 65%
“…A reduced HI antibody response against A/California/7/2009 (H1N1) was noted in healthy adults who had previously received a seasonal influenza vaccine. This finding has been presented before in the ferret model (17) as well as in clinical studies (18,19). The mechanism is still uncertain, but the following hypothesis may be considered.…”
Section: Discussionsupporting
confidence: 65%
“…This protective effect correlated with a reduction of H5N1 virus replication in the upper respiratory tract and was prevented by vaccination against H3N2 virus infection in three of eight ferrets (38%). This scenario resembles observations made in Canada, where subjects vaccinated against seasonal influenza in previous seasons were more likely to develop severe disease caused by infection with pandemic influenza A/H1N1(2009) viruses (17,40). However, the lack of heterosubtypic immunity in these patients was not confirmed.…”
Section: Discussionsupporting
confidence: 61%
“…[24][25][26] A recent meta-analysis found that prior receipt of seasonal influenza vaccination may have been associated with moderate protection against influenza A(H1N1)pdm09. 27 This study provides an opportunity to compare the risk of pandemic influenza infection among healthcare workers with and without a history of prior seasonal influenza vaccination.…”
Section: Resultsmentioning
confidence: 99%